التخطيط للاتصال في المؤسسة وفق منهجية إدارة المشروع - سالم، عطية الحاج Salem, Attiah Alhaj (جامعة الجزائر1 بن يوسف بن خدة, 2018)
The article seeks to present a set of concepts related to project management, and all the knowledge, techniques, competencies, and means that enable it to achieving the needs expressed in the required quality, and the adoption of the lowest possible cost, and at the best possible time. The aim of this project is to try to bring this down to the planning process of communication in the organization in such a way as to benefit from all these knowledge innovations available and possible to work with in the institution.
يبحث المقال في محاولة تقديم جملة من المفاهيم المرتبطة بإدارة المشروع، وكل ما تشير إليه من معارف، وتقنيات، وكفاءات، ووسائل تمكن من تحقيق الاحتياجات المعبر عنها بالجودة المطلوبة، وباعتماد أقل ما يمكن من التكلفة، وفي أحسن وقت ممكن. ويهدف من جانب آخر إلى محاولة إسقاط كل ذلك على عملية التخطيط للاتصال في المؤسسة بالشكل الذي يجعله يستفيد من كل هذه الابتكارات المعرفية المتوفرة والممكن العمل عليها في المؤسسة.
Keywords: علوم الإعلام والاتصال -- الاتصالات الإدارية -- المعلومات الإدارية -- إدارة المشروعات